Prevalence and pattern of risk factors for non-communicable diseases in urban population of Jaipur, Rajasthan - Kumar, Chabbil; Dobhal, Priyanka; Kashyap, Amita (International Journal Of Community Medicine And Public Health, 2019)
Background: Majority of the risk factors for NCDs are measurable and modifiable thus continuous surveillance of the levels and pattern of these risk factors is of fundamental importance. Taking cognizance of Jaipur city rapidly adopting to metropolitan culture; this study may mark an important milestone in surveillance activities and setting preventive priorities for NCDs in the state of Rajasthan. Aim of the study is to measure prevalence and associated variables of major risk factors for NCDs in the age group of 25-64 years. Methods: It is a cross sectional, descriptive study, conducted on 1454 person aged 25 to 64 years, residing in Jaipur city, from 1st June 2012 to 31st December 2013, using two steps of ‘standard WHO STEPS structured instrument’. Categorical data were expressed in form of percentage. Chi-square test was used to analyse difference in proportions. Continuous data were summarized in form of mean and SD. The differences in means were analysed by student’s t test. Results: At least one risk factor was present in all persons moreover 35% had multiple risk factors. Multiple risk factors were present even in 20% of relatively young adults (25-34 years). Tobacco and alcohol consumption was seen in 28% and 29% respectively. Standard of living index was associated with obesity, hypertension and low physical activity but not with alcohol use, smoking and daily consumption of fruit & vegetable. Male consumed more alcohol, indulged in less physical activity and smoked more than twelve times than females. Conclusions: Educating younger population for healthy lifestyle adoption and focused educational intervention with strict enforcement of existing laws will be helpful in controlling this epidemic of NCD.